2022
DOI: 10.1039/d2ce00633b
|View full text |Cite
|
Sign up to set email alerts
|

Photodegradation of naproxen using CuZnAl-layered double hydroxides as photocatalysts

Abstract: Naproxen (NPX) as a typical pharmaceutical and personal care products (PPCPs) is frequently detected in waters and difficult to remove effectively by conventional methods. Layered double hydroxides as highly Efficient...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 57 publications
0
2
0
Order By: Relevance
“…The best degradation efficiency for diclofenac acid achieved was 93% after 120 min [67]. CuZnAl−LDHs with different Zn/Cu/Al ratios was manufactured by the co-precipitation method and were successfully applied for the photodegradation of naproxen (NPX) [68]. Compared to ZnAlTi−LDHs and CuZnAl−LDHs, ZnNiFe−LDHs exhibited greater light adsorption capabilities, lower band gaps, and good surface dispersion, producing remarkable photocatalytic performance without any pre-processing or calcination [44].…”
Section: Pure-phase Ldhsmentioning
confidence: 99%
“…The best degradation efficiency for diclofenac acid achieved was 93% after 120 min [67]. CuZnAl−LDHs with different Zn/Cu/Al ratios was manufactured by the co-precipitation method and were successfully applied for the photodegradation of naproxen (NPX) [68]. Compared to ZnAlTi−LDHs and CuZnAl−LDHs, ZnNiFe−LDHs exhibited greater light adsorption capabilities, lower band gaps, and good surface dispersion, producing remarkable photocatalytic performance without any pre-processing or calcination [44].…”
Section: Pure-phase Ldhsmentioning
confidence: 99%
“…The energy band gap was reduced by 2.2 eV, and the ultrasonically catalyzed degradation of the pesticide imidacloprid was increased from 16% to 73%. 28 The doping of Cu d+ increased the oxygen vacancies in ultrathin ZnAl-LDH nanosheets, effectively promoting the adsorption and charge separation and transfer of N 2 molecules for the effective reduction of N 2 . 29,30 Rao et al found that the doping of unbalanced ions in the lattice led to the formation of oxygen vacancies (OVs) in the tissue nanoparticles, resulting in a highly stable removal effect.…”
Section: Introductionmentioning
confidence: 99%